INTEGRASI KUNJUNGAN LAPANGAN DAN EDUKASI HIDROPONIK DALAM PEMBELAJARAN BIOLOGI BAGI SISWA SMA 9 PADANG - Mildawati; Solfiyeni; Mairawita; Zozy Aneloi Noli; Feskaharny Alamsjah (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Field trip-based hydroponics education aims to introduce high school students to the practical application of biology in modern agriculture, bridging theoretical knowledge with real-world practice. Designed for students of SMA 9 Padang, this programme integrates biology lessons with hands-on hydroponic activities. It includes several key stages: initial socialisation to explain the programme's goals, field visits to hydroponic facilities for firsthand learning, and practical implementation of hydroponic systems at the school. The programme's effectiveness was assessed using questionnaires to evaluate students' understanding, interest, and practical skills before and after participation. The results highlighted significant improvements in students' comprehension of biology concepts, particularly regarding plant growth and hydroponic techniques. Additionally, the programme enhanced students' interest in sustainable agriculture practices. By combining experiential learning with classroom instruction, this initiative is expected to serve as a compelling model for applied biology education, promoting active engagement and deeper learning at the high school level.